2010
DOI: 10.1371/journal.pone.0009800
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β1 and MAP Kinases in the Antiproliferative Effect of Aspirin in Human Vascular Smooth Muscle Cells

Abstract: BackgroundWe aimed to test the antiproliferative effect of acetylsalicylic acid (ASA) on vascular smooth muscle cells (VSMC) from bypass surgery patients and the role of transforming growth factor beta 1 (TGF-β1).Methodology/Principal FindingsVSMC were isolated from remaining internal mammary artery from patients who underwent bypass surgery. Cell proliferation and DNA fragmentation were assessed by ELISA. Protein expression was assessed by Western blot. ASA inhibited BrdU incorporation at 2 mM. Anti-TGF-β1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…The results showed that the levels of plasma IL-35, IL-10 and TGF-β1 were dramatically decreased, whereas plasma IL-12 and IL-27 levels were significantly increased in patients with UAP and AMI compared with chest pain syndrome patients. Some studies found that aspirin could efficiently regulate the secretion of cytokines in vitro , whereas some showed contrary results [27][29]. In this study, we did not find a significant change in plasma levels of IL-35 and other cytokines after treatment with aspirin and clopidogrel, suggesting that a longer time is required to observe the effect of aspirin and clopidogrel on IL-35 production in vivo .…”
Section: Discussioncontrasting
confidence: 83%
“…The results showed that the levels of plasma IL-35, IL-10 and TGF-β1 were dramatically decreased, whereas plasma IL-12 and IL-27 levels were significantly increased in patients with UAP and AMI compared with chest pain syndrome patients. Some studies found that aspirin could efficiently regulate the secretion of cytokines in vitro , whereas some showed contrary results [27][29]. In this study, we did not find a significant change in plasma levels of IL-35 and other cytokines after treatment with aspirin and clopidogrel, suggesting that a longer time is required to observe the effect of aspirin and clopidogrel on IL-35 production in vivo .…”
Section: Discussioncontrasting
confidence: 83%
“…In order to examine if MIF plays a role in hypoxia-induced cell proliferation, we used bromodeoxyuridine (Brdu) incorporation assay[ 22 , 23 ] to study the proliferation of growth-arrested HUASMCs followed by co-treatment with specific MIF-siRNA (Santa Cruz Biotech, USA) and hypoxia (3% O 2 ) for 24 h. The specific MIF-siRNA could significantly inhibit MIF expression in HUVSMCs under both normoxia and hypoxia conditions (Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of hypoxia on cell proliferation was determined by the bromodeoxyuridine (BrdU) incorporation assay, as described previously [ 22 , 23 ]. Briefly, HUASMC cells were subcultured in 96-well plates and incubated with serum-free medium for 24 h in order to synchronize the cells in G 0 /G 1 phase.…”
Section: Methodsmentioning
confidence: 99%
“…[ 27 ] TGF-β1 was found to work through the p38 MAPK signal pathway but not JNK. [ 28 29 30 31 32 33 34 35 ] Thus, we postulated that p38, but not JNK, was involved in the LPS-induced acute pulmonary fibroproliferation and JNK inhibitor had no obvious effect on pulmonary fibrosis in ARDS.…”
Section: Discussionmentioning
confidence: 97%